Characterization of aerosol chemical composition and the reconstruction of light extinction coefficients during winter in Wuhan, China. (February 2020) - Liao, Weijie; Zhou, Jiabin; Zhu, Shengjie; Xiao, Anshan; Li, Kuan; Schauer, James J.
Abstract: To evaluate light extinction contributions of aerosol chemical constituents and their impacts on atmospheric visibility, the PM2.5 and its chemical components, light scattering (bsp ) and absorption (bap ) were continuously measured in Wuhan from January to February 2018. The average of PM2.5 concentration, bsp and bap were 96.5 ± 13.7 μg m −3, 564 ± 124 Mm −1 and 44 ± 8 Mm −1 during polluted days, respectively, which was about 2.0, 2.1 and 1.6 times higher than those of clean days, respectively. Compared with the clean days, the increase of the mass concentrations of SNA (SO4 2−, NO3 −, NH4 + ) during polluted days was higher than those of organic (OC) and elemental (EC) carbon, indicated the increase of SNA was the main cause of air pollution. The PM2.5 concentration threshold was 66 μg m −3, corresponding to the visibility lower than 10 km. The revised Interagency Monitoring of Protected Visual Environments (IMPROVE) algorithm was used to reconstruct the light extinction coefficient (bext ) in Wuhan. The sum of light extinction coefficients of (NH4 )2 SO4, NH4 NO3 and organic matter (OM) accounted for 70.5% and 83.9% of bext during clean and polluted days, respectively. The backward trajectory and potential source contribution function (PSCF) analysis revealed that regional transport accounted for 55.6% of the total airflow, which originated from south, northwest and west of Wuhan. The increases of (NH4 )2 SO4 and NH4 NO3 concentrations, emitted from local vehicle exhaust and coal combustion, and their hygroscopic growth in ambient were the major causes of pollution in Wuhan. Highlights: Light extinction contributions of dominant chemical components were determined. Visibility was 10 km when PM2.5 concentration was 66 μg m −3 in winter in Wuhan. Sulfate, Nitrate and OM were the dominant contributors to bext . Contribution of regional transport was higher than that of local transport.